Part IV Italy: Case 12 Passeiertal/Val Passiria - Volgger, Michael; Pichler, S.; Herntrei, M. (2015)
The case of Passeiertal/Val Passiria illustrates how typologies of governance forms help to differentiate cases with concentrated authority from cases with an even distribution of power. In particular, it exemplifies how the interplay between DMOs and powerful private businesses can improve the competitive position of a destination. First, Passeiertal/Val Passiria has managed to develop a common strategy in collaboration with the biggest private player. Second, the whole destination is positioned with the themes driven by the player. The case also shows that property rights theory and principal agent theory may provide useful explanations as to how sustainable destination governance can be improved in situations of significant power asymmetries.